A study-of-Religion(s)-Based Religion Education: Skills, Knowledge, and Aims - Kjeldsen, Karna (CEPS journal, 2019)
Different approaches to religion education have been in place for a long time or developed more recently to meet growing religious and cultural plurality in European countries and schools. In this article, I summarise and discuss basic principles for a study-of-religion(s) approach to religion education, adding arguments and perspectives from critical theories about education in general. I shall also argue that national curricula for, respectively, religion education in Sweden and History in Denmark indicate that analytical-critical skills can be a central part of religion education in elementary and lower secondary public schools. The structure of the article is based on a modified version of the ‘map of history’ developed by the scholar of education and history education Rosie Turner-Bisset who has formulated principles for teaching History in primary schools. The model will be used as a framework, for systematising and discussing key principles of a study-of-religions approach to religion education with reference to three categories: 1) attitudes, 2) skills and concepts, and 3) knowledge.